2018
DOI: 10.3892/mmr.2018.9393
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotection of dapagliflozin in human renal proximal tubular cells via the inhibition of the high mobility group box 1‑receptor for advanced glycation end products‑nuclear factor‑κB signaling pathway

Abstract: Sodium‑glucose co‑transporter 2 (SGLT2) inhibitors are recently developed oral hypoglycemic agents, which act on renal proximal tubules by reducing the reabsorption of glucose and increasing the excretion of glucose in the urine. However, the mechanism underlying renoprotection has not been fully elucidated. Previous studies have indicated that the expression of high mobility group box 1 (HMGB1) increased in patients with kidney disease, and may result in renal damage through the activation of nuclear factor‑κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 22 publications
3
39
0
2
Order By: Relevance
“…In short, major pathophysiologic mechanisms underlying increased arterial stiffness in diabetes mellitus include the formation of advanced glycation end products (AGEs) on the arterial wall, inducing cross‐linking of collagen molecules and subsequent loss of collagen elasticity, increased activity of renin‐angiotensin‐aldosterone system (RAAS), chronic inflammation, enhanced oxidative stress, and endothelial dysfunction (Figure ) . It has been therefore shown (mainly in experimental models) that SGLT‐2 inhibition decreases the expression of AGEs and their receptor (RAGE), while it also suppresses oxidative stress and inflammatory response . It has been also demonstrated that SGLT‐2 inhibition might provide a significant, beneficial effect on endothelial dysfunction in T2DM, although results are contradictory in shorter duration studies .…”
Section: Sglt‐2 Inhibitors and Arterial Stiffness: A New Place Under mentioning
confidence: 99%
“…In short, major pathophysiologic mechanisms underlying increased arterial stiffness in diabetes mellitus include the formation of advanced glycation end products (AGEs) on the arterial wall, inducing cross‐linking of collagen molecules and subsequent loss of collagen elasticity, increased activity of renin‐angiotensin‐aldosterone system (RAAS), chronic inflammation, enhanced oxidative stress, and endothelial dysfunction (Figure ) . It has been therefore shown (mainly in experimental models) that SGLT‐2 inhibition decreases the expression of AGEs and their receptor (RAGE), while it also suppresses oxidative stress and inflammatory response . It has been also demonstrated that SGLT‐2 inhibition might provide a significant, beneficial effect on endothelial dysfunction in T2DM, although results are contradictory in shorter duration studies .…”
Section: Sglt‐2 Inhibitors and Arterial Stiffness: A New Place Under mentioning
confidence: 99%
“…29,30 In addition to decreasing hypoxic stress, SGLT2 inhibitors may also increase cellular adaptation to hypoxia through cellular signalling, decreased inflammation, and stabilization of kidney tubular and mesangial cells. [31][32][33] Further research is needed to better elucidate the mechanism of renoprotection, as well as ongoing concerns for other adverse events associated with SGLT2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies using immortalized human tubular epithelial cells (e.g., HK2 cell line) [25][26][27][28], murine tubular epithelial cells [29] or non-renal cells [30,31] investigated either the effects of empa-or of dapagliflozin. Some of them have shown that SGLT2 inhibition reduced the release of inflammatory or fibrotic factors induced by high glucose levels [25][26][27], others found effects on oxidative stress responses [26,30,31]. Our current study looked at whether high glucose induced changes were influenced by either of the two gliflozins.…”
Section: Discussionmentioning
confidence: 99%